A Survey on Storage Virtualization and its Levels along with the Benefits and Limitations - Bhore, Pratik Rajan (International Journal of Computer Sciences and Engineering, 2025)
This study paper revolves around the impact of virtualization at the various layers of storage stack. There is a rapid growth in the storage capacity, and hence the processing power in the respective enterprises storage appliances coupled with the requirements for high availability and it needs a Storage Area Network (SAN) architecture for providing the storage and performance elements here. The Storage Virtualization provides us with a combination and management of storage resources for Storage Area Network with multiple servers as well as the storage devices. The main aim for storage virtualization is its necessity to be inexpensive and not affect the performance. Currently, the storage virtualization is displayed at three different architectural levels: (1) the storage device, (2) the host and (3) the SAN fabric hardware as a central management unit. This paper further provides us with more information on the storage virtualization levels that are part of its architecture. Each of these levels that we will see grants us with particular advantages and benefits but is also limited in their capabilities gets considered as their drawbacks or limitations.